Enhancing Students’ Speaking Skill By Utilizing Spinning Wheel at MTs Al-Ma'arif Kabupaten Serang (Conference on English Language Teaching, 2023)
This study aims to measure the improvement of students’ ability in describing a particular person after giving treatment by using spinning wheel media at Eighth Grade Students of MTs Al-Ma'arif Kabupaten Serang.  In this study, the researcher proposed a research namely “Does spinning wheel can enhance students’ speaking skills?” to answer  the research question, the researcher used quasi experimental research methods with data collection techniques through observation, interviews, speaking tests (pre-test, post-test) as well as documentation. There were two classes involved in this study, namely class VIII A which acted as control group and class VIII B which acted as experimental group. The final findings of this study reveals that the result of t-test was 4.2  meanwhile the value of t-table with degree of significance 5% that was 1.67 In short, the result of t-test showed that t0 > tt or  4.2 > 1.67 In brief, t-test showed that Ha or alternative hypothesis was accepted. Meanwhile, H0 or null hypothesis was rejected. In other words, It can be drawn a conclusion that there is a significant effect of using spinning wheel media to enhance students’ speaking skill. In addition, the mean score of pre-test score of students in the experimental class was 62 while in the control class was 60.6 and the post-test score of the experimental class was 73.5 while the control class was 68.8.